Estimating the Cost-Competitiveness of Recycling-Based Geopolymer Concretes - Annastiina Rintala; Jouni Havukainen; Mariam Abdulkareem (Recycling, 2021)
The cement industry is a major contributor to greenhouse gas emissions on a global scale. Consequently, there has been an increasing interest, in both academia and business, in low-carbon concretes in which Ordinary Portland Cement (OPC) is partially or fully replaced with industrial side streams. However, the realization of the environmental benefits of such materials depends on how competitive they are in the construction market, where low costs are a major competitive factor. This is not straightforward, as many types of concretes exist. Raw material prices vary, and costs can be influenced by governmental regulations via carbon pricing. This study presents a case study estimating the cost prices of four different geopolymer concretes with different material compositions and carbon footprints, considering the raw material price variability and the potential impact of carbon emissions regulation (carbon price). The case study demonstrates how material mix cost comparisons can be made openly and systematically. The results imply that carbon pricing, at the rates currently applied, does not significantly change the cost price difference between traditional and geopolymer concretes. Instead, cost-competitiveness of low carbon concretes depends heavily on the material mix type and the availability of critical side streams.